The effect of water immersion on the shear bond strength between chairside reline and denture base acrylic resins: Basic science research - Azevedo, Andrea [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley, 2007)
Purpose: The effect of water immersion on the shear bond strength (SBS) between 1 heat-polymerizing acrylic resin (Lucitone 550-L) and 4 autopolymerizing reline resins (Kooliner-K, New Truliner-N, Tokuso Rebase Fast-T, Ufi Gel Hard-U) was investigated. Specimens relined with resin L were also evaluated. Materials and Methods: One hundred sixty cylinders (20 × 20 mm) of L denture base resin were processed, and the reline resins were packed on the prepared bonding surfaces using a split-mold (3.5 × 5.0 mm). Shear tests (0.5 mm/min) were performed on the specimens (n = 8) after polymerization (control), and after immersion in water at 37°C for 7, 90, and 180 days. All fractured surfaces were examined by scanning electron microscopy (SEM) to calculate the percentage of cohesive fracture (PCF). Shear data were analyzed with 2-way ANOVA and Tukey's test; Kruskall-Wallis test was used to analyze PCF data (α = 0.05). Results: After 90 days water immersion, an increase in the mean SBS was observed for U (11.13 to 16.53 MPa; p < 0.001) and T (9.08 to 13.24 MPa, p = 0.035), whereas resin L showed a decrease (21.74 MPa to 14.96 MPa; p < 0.001). The SBS of resins K (8.44 MPa) and N (7.98 MPa) remained unaffected. The mean PCF was lower than 32.6% for K, N, and T, and higher than 65.6% for U and L. Conclusions: Long-term water immersion did not adversely affect the bond of materials K, N, T, and U and decreased the values of resin L. Materials L and U failed cohesively, and K, N, and T failed adhesively. © 2007 by The American College of Prosthodontists.
Keywords: Acrylic resins; Relining; Shear strength; Water storage; acrylic acid resin; kooliner; Lucitone; methacrylic acid derivative; polymer; silastic; Tokuso Rebase Fast; truliner; Ufi gel; unclassified drug; water; adhesion; chemistry; dental bonding; denture; human; immersion; materials testing; mechanical stress; scanning electron microscopy; shear strength; time; Acrylic Resins; Adhesiveness; Dental Bonding; Denture Bases; Denture Liners; Denture Rebasing; Humans; Immersion; Materials Testing; Methacrylates; Microscopy, Electron, Scanning; Polymers; Shear Strength; Silicone Elastomers; Stress, Mechanical; Time Factors; Water